Selection and Preparation of Planting Material for Successful Hop Production in Florida - Shinsuke Agehara; Aleyda Acosta-Rangel; Mariel Gallardo; Gary Vallad (EDIS)
Hops (Humulus lupulus L.), an essential ingredient in beer, have potential to develop as a viable alternative crop in Florida. In our surveys, many breweries have expressed strong interest in using locally grown hops. However, hop production is plagued by many diseases, most of which were inadvertently introduced through the movement of contaminated planting material. The primary purposes of this new 7-page article are to prevent the introduction of these diseases into the state and to provide recommendations for selecting and preparing planting material for successful hop production in Florida. This publication of the UF/IFAS Horticultural Sciences Department is part of a larger series that will review the challenges of hop production, based on research experience at the UF/IFAS Gulf Coast Research and Education Center (UF/IFAS GCREC) in Balm, FL. https://edis.ifas.ufl.edu/hs1381